Kodaly teachers’ perception on aural and Musicianship training in Malaysia / Low Siew Moon - Low , Siew Moon (2020)
This study investigated the perception of three experienced music teachers in Malaysia who apply Kodály method in their music teaching. A qualitative research approach was employed to investigate how aural and musicianship training in Kodály method being carried out in Malaysia. Narrative interviews were conducted for interviewees to share their teaching experiences using Kodály method. There are six core philosophies in Kodály method as follows: (1) Music literacyis the right for everyone, (2) The most authentic instrument is human voice, (3) Music education should start as young as possible, (4) Singing is the basis for all music, (5) Folk songs is the ‘musical mother tongue’, (6) Child-centered approach is vital (Casarow, 2015). This study aims to understand teacher’s training in Kodály teaching method in Malaysia. Kodály teacher and students have to prepare, present and practice when planning for music lesson. Perception of three music teachers in Malaysia who apply Kodály method in their music teaching were investigated. Data collected was analyzed and transcribed for discussion. In general, the result showed that Kodály method is a way of teaching that stimulates learners’ innate ability and can help to improve students’ aural ability and musicianship.